Reconstruction of the late first millennium AD harbor site of Sembiran and analysis of its tradeware. (24th January 2022) - Calo, Ambra; Moffat, Ian; Bulbeck, David; Dupoizat, Marie France; Simyrdanis, Kleanthis; Walker, Chester P.; Bawono, Rochtri Agung; Prasetyo, Bagyo
Abstract: The site of Sembiran on the northern coast of Bali was an important trading harbor with demonstrated intensive links to the Indian subcontinent, the Western Indian Ocean, and Mainland Southeast Asia between the second century BC and the second century AD. Using a combination of excavation and geophysical survey, we have newly mapped a dense network of subsurface structures, which we interpret to be foundations for harbor infrastructure dated to the eighth to ninth centuries AD that were subsequently covered by shoreline aggradation. An assemblage of eighth to twelfth centuries AD Chinese tradeware in dated contexts from our excavations of these shoreline structures and additional trenches further inland suggests a renewal in trade activities at Sembiran, coinciding with the growth of Chinese maritime trade in Island Southeast Asia.